Context and Time Matter: Effects of Emotion and Motivation on Episodic Memory Overtime. (8th April 2018) - Sun, Qing; Gu, Simeng; Yang, Jiongjiong
Abstract : Previous studies have shown that compared with neutral cues, stimuli with positive and negative/stressful contexts or reward and punishment cues are remembered better. However, it is unclear whether the enhanced effect differs in emotion or motivation dimensions and the passage of time. We addressed these issues by manipulating different contextual cues for neutral words at different time intervals. In experiment 1, subjects were asked to learn words with picture contexts in positive, negative/stressful, and neutral valences and were tested by old/new word recognition and contextual judgment 10 min, 1 day, and 1 week later. In experiment 2, the reward and punishment motivations were manipulated by monetary cues during learning. Word recognition and contextual judgment were assessed 10 min, 1 day, 1 week, and 1 month after the study. Compared with negative and punishment conditions, the words in positive and reward contexts were recognized better at shorter intervals, which was associated with recollection process. In contrast, the words in negative and punishment contexts were recognized better at longer intervals, which was mainly associated with familiarity process. These results clarified how different dimensions of emotional and motivational contexts influence memory at short and long intervals and highlighted the role of contextual features in memory formation and consolidation.